تكنولجيا التعليم ودوره في تعليم اللغة العربية للناطقين بلغة أخرى - Mubarak, Faisal (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2019)
Arabic is one of the seven world languages recognized by the United Nations. Besides being an international language, the existence of Arabic in Indonesia cannot be separated from the language of Religion. The entry of Arabic in Indonesia is accompanied by the presence of Islam. Arabic in Indonesia has a very important influence. As a world language, Arabic is a compulsory subject that is taught in our country starting from the Ibididaiyah level to the university level, but the results are far from what is expected. This is none other than not because the results of language acquisition in most Islamic Education institutions from elementary to tertiary level are still low. In addition, the atmosphere and tradition of Arabic speaking is very rarely found in the Education environment. Various kinds of analysis that reveal the low language ability of children, starting from the methodology to teaching materials and materials and also that are not less important are media or learning technology. Through this research the author wants to map the extent of the influence of the use of media for teaching Arabic for non-Arabs.